Safety of same-day discharge after lead extraction procedures - Dagher, Lilas; Tfaily, Mohamad Ali; Vavuranakis, Michael; Bhatia, Neal Kumar; Westerman, Stacy B.; Shah, Anand D.; Lloyd, Michael S.; Leal, Miguel; De Lurgio, David B.; Merchant, Alam; Panagopoulos, Anastasios; Patel, Anshul M.; et al. (Heart rhythm, 2023)
Same-day discharge (SDD) after cardiovascular procedures is rapidly gaining ground. We sought to evaluate the safety of SDD after transvenous lead extraction (TLE). We performed a retrospective chart review of patients who underwent elective TLE between January 2020 and October 2021 at our institution. The primary outcome was SDD, and major procedural complications and readmissions within 30 days of the procedure were secondary outcomes. In this analysis of 111 patients who underwent elective TLE, 80 patients (72%) were discharged on the same day (SDD group) while 31 patients (28%) stayed overnight (overnight group). Lead malfunction was the most common indication for TLE in both groups. Patients in the overnight group were more likely to have a lead dwell time of ≤10 years than those in the SDD group (38.7% vs 20% of all leads in each group; P = .042), have laser sheaths used for extraction and a higher number of leads extracted. No major complications were reported in both groups. In a multivariate analysis, lower body mass index and the use of laser sheath during TLE were predictors of overnight stay. Patients who underwent a procedure using advanced extraction techniques were 3.5 times more likely to stay overnight (95% confidence interval 1.27–9.78; P = .016). In appropriately selected patients undergoing elective lead extraction, SDD is feasible and safe. Higher body mass index, fewer extracted leads, shorter lead dwell times (<10 years), and less frequent use of laser-powered extraction sheaths were associated with an increased likelihood of SDD.